Influence Of Digital Marketing on The Buying Behaviour of Consumers - Usha Rani Nagar; Hari Shankar Shyam (Educational Administration: Theory and Practice, 2024)
The market has been compelled to transition from old-style forms to innovative digital marketing due to the unprecedented surge in online usage in this fiercely competitive environment. Digital marketing is the practice of advertising using sophisticated channels such as emails, mobile applications, content creation, and search engine optimization. It provides them with a wide array to choose from globally available goods and services. Customers may now access products both domestically and internationally, and digital marketing is the sole thing that has made this feasible. People have become more technology-driven and use their smart devices like phones, tablets, iPads, and laptops for exploring, comparing, and buying desired stuff digitally. It saves time, cost, and effort. Due to the current growth and development of online usage and the dedication of buyers and suppliers, customers’ approaches are evolving; businesses ought to do a thorough analysis of this, and those who fail to recognize these evolving digital marketing strategies lose out on customers. Thus, the purpose of this research study is to scrutinize how digital marketing affects consumers’ buying preferences. Data was gathered from 170 people employed in the marketing sector in Delhi through a closed-ended questionnaire. This paper helps marketers understand different marketing strategies like content creation, search engine optimization, email marketing, viral marketing, mobile marketing, and so on. It also provides marketing managers with insights into the mistakes that they often make while designing marketing strategies and learn from them to achieve their targets and boost their sales.